Naringin Effect on SARS-CoV-2 Pseudovirus Entry and Spike Mediated Syncytia Formation in hACE2-overexpressing Cells - Septisetyani, Endah Puji; Prasetyaningrum, Pekik Wiji; Paramitasari, Komang Alit; Suyoko, Ahmad; Himawan, Alayna Lillahida Indri; Azzahra, Salsabila; Wisnuwardhani, Popi Hadi; Anam, Khairul; Ramadani, Ratna Dwi; Santoso, Adi; Ningrum, Ratih Asmana; Herawati, Neng; Rubiyana, Yana (HAYATI Journal of Biosciences, 2024)
A molecular docking study demonstrates the interaction between naringin, a citrus flavonoid, with SARS-CoV-2 spike RBD. Nevertheless, in vitro investigation of the inhibitory effect of naringin on SARS-CoV-2 entry and syncytia models has yet to be carried out. We synthesized VSV∆G-GFP/Spike* pseudovirus (PSV) as a SARS-CoV-2 model by pseudotyping VSV∆G-GFP/S* in BHK-21 cells overexpressing the SARS-CoV-2 spike glycoprotein. In the SARS-CoV-2 PSV entry assay, we utilized CHO-K1 cells transfected with hACE2 plasmid, which were then treated with naringin and SARS-CoV-2 PSV/naringin. After 16-18 h incubation, PSV internalization represented by the GFP signal was observed under a fluorescence microscope. Immunofluorescence staining was also performed to probe the SARS-CoV-2 spike and confirm the PSV entry. We performed a syncytia assay using 293T cells co-transfected with SARS-CoV-2 spike/hACE2. Six hours after transfection, the cells were treated with naringin and incubated for another 16-18 hours. Then, we observed syncytia using a phase contrast microscope. Based on fluorescence foci quantification, the results indicated that naringin might inhibit SARS-CoV-2 PSV entry at a concentration of 100 µM (P<0.05). However, naringin did not prevent syncytia formation compared to solvent control. These PSV entry and syncytia assay results suggested that naringin potentially inhibited SARS-CoV-2 viral infection but not cell-to-cell viral transmission.